2011
DOI: 10.2174/138920011796504536
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine - Metabolic Functions and Meaning in Humans Life

Abstract: L-Carnitine is an endogenous molecule involved in fatty acid metabolism, biosynthesized within the human body using amino acids: L-lysine and L-methionine, as substrates. L-Carnitine can also be found in many foods, but red meats, such as beef and lamb, are the best choices for adding carnitine into the diet. Good carnitine sources also include fish, poultry and milk. Essentially, L-carnitine transports the chains of fatty acids into the mitochondrial matrix, thus allowing the cells to break down fat and get e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
179
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(183 citation statements)
references
References 0 publications
1
179
0
3
Order By: Relevance
“…Oral L-carnitine supplementation has been reported to have benefi cial effects on exercise capacity in clinical populations and is considered a potential ergogenic aid for endurance athletes (Muller et al, 2002). Although dietary reference intakes for L-carnitine have not been established, beef is one of the best dietary sources of L-carnitine (Demarquoy, 2011;Pekala et al, 2011). L-carnitine content of beef steaks in our study averaged 316 mg/serving (100 g).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Oral L-carnitine supplementation has been reported to have benefi cial effects on exercise capacity in clinical populations and is considered a potential ergogenic aid for endurance athletes (Muller et al, 2002). Although dietary reference intakes for L-carnitine have not been established, beef is one of the best dietary sources of L-carnitine (Demarquoy, 2011;Pekala et al, 2011). L-carnitine content of beef steaks in our study averaged 316 mg/serving (100 g).…”
Section: Resultsmentioning
confidence: 66%
“…Carnitine, sometimes regarded as a vitamin-like substance (Pekala et al, 2011), is an essential molecule in fatty acid oxidation, mediating the transport of medium-/ long-chain fatty acids into the mithocondrial matrix (Demarquoy et al, 2004) and preventing accumulation of toxic intermediate compounds by facilitating their transport out of the mitochondria. Oral L-carnitine supplementation has been reported to have benefi cial effects on exercise capacity in clinical populations and is considered a potential ergogenic aid for endurance athletes (Muller et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…We also found that all identified carnitines and carnitine derivatives were increased with CR, and this has implications for longevity, as in Drosophila L‐carnitine shows a highly significant decline with age (Hoffman et al ., 2014). L‐carnitine shuttles fatty acids across the mitochondrial membrane, where they can be processed by β‐oxidation enzymes to ultimately generate ATP (Flanagan et al ., 2010; Pekala et al ., 2011). Studies have shown that L‐carnitine supplementation has positive effects in obese and diabetic humans, as well as benefits in cats and mice (Levin et al ., 1999; Blanchard et al ., 2002; Mingorance et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Carnitine transports long‐chain fatty acids into the mitochondria for β‐oxidation and protects the myocardium against ischaemic injury, the occurrence of angina, diastolic dysfunction, and HF 2, 3. Carnitine deficiency results in impaired mitochondrial β‐oxidation, decreased glucose oxidation, and accelerated cellular apoptosis 4, 5.…”
Section: Introductionmentioning
confidence: 99%